MARRIAGE CONFLICT REVIEWED FROM THE SOCIO-ECONOMIC STATUS OF THE FAMILY - Fachrina, Fachrina; Damsar; Alfan Miko; Jendrius (Universitas Andalas, 2025)
Married life is often characterized by various conflicts. Marital conflicts that occur in each married couple will be different and unique. One of the factors related to the dynamics of marital conflict is the socioeconomic status of the family. The study aimed to describe the forms, causes, and impacts of marital conflict in high and low social classes. Researchers used qualitative methods for data collection, namely structured and in-depth interviews, observations of informants from 10 families living in Padang City. Informants were determined intentionally (purposive sampling) based on education, occupation, income of the married couple, and assets owned. The data obtained through structured interviews are presented through frequency tables and explained in more depth based on the data and information collected through in-depth interviews and observations. The data is interpreted qualitatively by combining existing categories to create descriptions based on relevant literature studies. The results of the study identified 6 families from high social class and 4 families from low social class. Conflicts between spouses, ranging from quarrels to domestic violence, were observed across both high and low socio-economic classes. However, the nature of the conflicts differed, with high social class conflicts mainly involving psychological domestic violence, while those in the lower social class involved physical, economic, and psychological forms of violence. The cause of marital conflict at high social classes tends to be due to differences in priorities. The wife wants the presence and attention of her husband more, while the husband prioritizes work or career achievement and hobbies as a status symbol. Conflict arises related to pressure to maintain a lifestyle according to social status. The causes of conflict at low social classes are dominated by financial pressure, division of household tasks, childcare, and home atmosphere. In general, marital conflict disrupts emotional conditions such as anxiety, stress/trauma. Physically healthy, the intensity of interaction with the partner is decreasing.